(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gender equality is at the heart of human rights law. It is one of the pillars of the United Nations’2030 Agenda for Development, and it is deemed essential to all areas of development. Gender equalityimplies that women, men, and transgender individuals have equal access to education, healthcare,economic resources, employment, leadership positions, involvement in political life and decision-making,and a role in the economic, political, and social growth of a nation. Gender equality signifies that the needsand interests of women, men, and transgender people are taken into account, and that everyone is free tomake their own decisions without regard to social conventions or biases regarding gender roles. Men andwomen have equal rights, yet there is still a gap that impacts people in different nations to differingdegrees throughout the world. It is women and transgender people who bear the brunt of thisdiscrepancy. As a result of the growing awareness of gender problems, transgender people’s genderinequities are now being emphasised. Transgender persons are denied their basic human rights as aresult of patriarchal societal standards. This is a big roadblock in the way of the sustainable growth thatwe all desire. India’s gender equality is examined in this research. That said, there’s a long way to goeven though this is changing in many areas of the world. Despite India’s progress and economicgrowth, gender inequality is still a major problem in the country.... From an early age, teachingyoungsters about the need of gender equality may have a good impact. To truly achieve genderequality, it is necessary to have an integrated strategy that includes women, transgender people, andmen working side by side.